Determination of the tricritical point, H–T phase diagram and exchange interactions in the antiferromagnet MnTa2O6. (13th April 2022) - R, Maruthi; Seehra, Mohindar S; Ghosh, Sayandeep; Medwal, Rohit; Rawat, Rajdeep S; Weise, Bruno; Choi, Eun Sang; Thota, Subhash
Abstract: Using the analysis of the temperature and magnetic field dependence of the magnetization ( M ) measured in the temperature range of 1.5 K to 400 K in magnetic fields up to 250 kOe, the magnetic field-temperature ( H – T ) phase diagram, tricritical point and exchange constants of the antiferromagnetic MnTa2 O6 are determined in this work. X-ray diffraction/Rietveld refinement and x-ray photoelectron spectroscopy of the polycrystalline MnTa2 O6 sample verified its phase purity. Temperature dependence of the magnetic susceptibility χ (= M / H ) yields the Néel temperature T N = 5.97 K determined from the peak in the computed ∂( χT )/∂ T vs T plot, in agreement with the T N = 6.00 K determined from the peak in the C P vs T data. The experimental data of C P vs T near T N is fitted to C P = A | T − T N | − α yielding the critical exponent α = 0.10(0.13) for T > T N ( T < T N ). The χ vs T data for T > 25 K fits well with the modified Curie–Weiss law: χ = χ 0 + C /( T − θ ) with χ 0 = −2.12 × 10 −4 emu mol −1 Oe −1 yielding θ = −24 K, and C = 4.44 emu K mol −1 Oe −1, the later giving magnetic moment μ = 5.96 μ B per Mn 2+ ion. This yields the effective spin S = 5/2 and g = 2.015 for Mn 2+, in agreement with g = 2.0155 measured using electron spin resonance spectroscopy. Using the magnitudes of θ and T N and molecular field theory, the antiferromagnetic exchange constants J 0 / k B = −1.5 ± 0.2 K and J ⊥ / k B = −0.85 ± 0.05 K for Mn 2+ ions along the chain c -axis and perpendicular to the c -axis respectively are determined. The χ vs T data when compared to the prediction of a Heisenberg linear chain model provides semiquantitative agreement with the observed variation. The H – T phase diagram is mapped using the M – H isotherms and M – T data at different H yielding the tricritical point T TP ( H, T ) = (17.0 kOe, 5.69 K) separating the paramagnetic, antiferromagnetic, and spin-flop phases. At 1.5 K, the experimental magnitudes of the exchange field H E = 206.4 kOe and spin-flop field H SF = 23.5 kOe yield the anisotropy field H A = 1.34 kOe. These results for MnTa2 O6 are compared with those reported recently in the isostructural MnNb2 O6 .